Forage biomass and nutrient quality in brown midrib (BMR) compared to conventional sorghum: A meta-analysis approach. - Widodo, Slamet; Indriatama, Wijaya Murti; Anggraeny, Yenny Nur; Sholikin, Mohammad Miftakhus; Jayanegara, Anuraga; Wahyono, Teguh (Journal of Advanced Veterinary and Animal Research, 2025)
Objectives: The primary objective of this study is to provide a comprehensive analysis of the differences between conventional and brown midrib (BMR) sorghum in terms of biomass, nutrient quality, nutrient digestibility, and animal performance. Materials and Methods: A comprehensive database was created by integrating 73 datasets from 29 articles. The different studies were denoted as random effects, while the BMR sorghum variety was described as a fixed component. Afterward, these two aspects were calculated utilizing a linear mixed model. Results: According to the findings of the present meta-analysis, conventional sorghum produces higher quantities of forage and grain biomass in comparison to BMR (p < 0.001). As expected, BMR sorghum has a lower content of neutral detergent fiber (NDF), acid detergent fiber, and lignin compared to conventional sorghum (p < 0.001). The digestibility of BMR sorghum performed better than conventional sorghum (p < 0.001), especially for NDF digestibility (54.98% vs. 47.37%). BMR shows suitability as a fodder option for dairy cows due to its superior milk yield compared to conventional sorghum (15.04 vs. 14.06 kg/day; p < 0.01). Conclusion: In conclusion, BMR sorghum produces higher biomass compared to conventional sorghum. Nevertheless, in terms of nutrient quality and digestibility, BMR sorghum is the most optimal choice. The results will significantly improve animal performance. J. Adv. Vet. Anim. Res., 12(1): 157–168, March 2025 http://doi.org/10.5455/javar.2025.l883